Analysis of BPJS Drug Inventory Control Using ABC-VEN Methods at Dr. Moewardi Surakarta Hospital in 2023 - Suhailah, Dhia; Peranginangin, Jason Merari; -, Iswandi (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Background: The implementation of JKN by BPJS Kesehatan, drug inventory management has become a crucial thing to ensure the efficiency and effectiveness of healthcare services. However, delays in BPJS claims these payments often disrupt drug procurement in hospitals. This study is aimed to prevent stock outs so that an effective inventory control method is needed at Dr. Moewardi Surakarta Hospital.Objectives: This study is aimed to analyze the management of BPJS drugs at the Pharmacy Installation of Dr. Moewardi Surakarta Hospital using the ABC-VEN, dan EOQ methods to optimize inventory control, ordering, and, storage.Methods: This descriptive-analytical study used retrospective data from pharmacy record documents, inventory systems, stock levels, usage, costs, and interview results. Data accuracy was ensured through triangulation, cross-checking records with financial documents, and respons of interviews in 2023. The inventory value was calculated by multiplying the quantity of drugs procured and remaining stock (on their own puchasing prices) at the end of the year. Inventory Turnover Ratio was calculated by dividing the COGS by the average inventory value. The data were analyzed using Microsoft Excel software version 2021.Results: Findings showed that ABC-VEN methods were 8% of drugs which were classified as AV, 6% as BV, 43% as CV, 5% as AE, 5% as BE, and 57% as CE out of 288 items, with CE dominating. The final inventory value was Rp 6,947,818,985 with an ITOR of 7.53 times per year.Conclusion: The findings show that the ABC-VEN method can improve inventory control, reduce stockouts, and align drug procurement with finance.